Interpretation of Verses on the Law of Marriage between Muslims and Non-Muslims (Musyrik, Kafir and Ahl Al-Kitab) - Moh Najib; U. Abdurrahman; Ayi Sofyan (West Science Law and Human Rights, 2023)
The MUI's fatwa in the Second National Deliberation on May 26 – June 1, 1980, on Mixed Marriage stipulates that "the marriage of a Muslim woman with a non-Muslim man is unlawful; A Muslim man is forbidden to marry a non-Muslim woman. The research method used is the descriptive method of content analytics, or document analysis techniques, or content analysis by collecting information and views, analysis of interpretations and opinions, in manuscripts, literature, or books of interpretation. The result found that the interpretation of the verses of the Qur'an that stipulates the law prohibiting marriage between Muslims and non-Muslims is the interpretation of Sura al-Baqarah verse 221 which stipulates that Muslims are prohibited from marrying non-Muslims and reveals that Ahl al-Kitab women are allowed to be married by Muslim men. And also, the interpretation of sura al-Mumtahanah verse 10, and sura al-Tawbah verses 30-31, and reinforced by other narrations, which implies that the legal provisions of marriage between Muslims and non-Muslims are haram, including the law of marriage between a Muslim man and a woman Ahl al-Kitab is haram.